A review: Posture and movement control methods to determine ergonomic risks in workers - Ortiz-Navarro, Juan Luis; López-Arias, Giovanni David; Chauca-Huete, Julio Luis; Estrada-Espinoza, Johan Alexander; Cruz-Aguilar, Ariana Alisabel (LACCEI, 2024)
Over the years, ergonomics has evolved from a focus on human factors to encompassing activity ergonomics, being applied to multiple industries. This significantly affects the quality of life of employees. In this regard, a systematic literature review was proposed on posture and movement control methods to determine ergonomic risks for workers. This study employs the PRISMA method for the systematic review. Inclusion and exclusion criteria were used for eligibility. The results show that the year with the highest annual scientific production was 2023, with 5 published studies, while the highest average number of total citations per article was in 2020. Furthermore, in the keyword frequency analysis, the words "ergonomics" and "human factors" had the highest repetitions. It was also identified that the Swiss journal Sensors published 4 articles on the study topic, showing a deep interest in the subject in that journal. A three-field plot was used to analyze the relationship between keywords, authors, and journals. In the content analysis, instruments, approaches, descriptions, ergonomic postures, samples, and the level of ergonomic risk were evaluated, with all the information compiled in a matrix. It is concluded that virtual reality technology showed positive potential in improving working conditions, where employees feel better knowing their ergonomic status through augmented reality simulations and control and analysis methods such as OWAS, RULA, and REBA. Finally, technology can be a valuable part of the solution; however, effective application and correction of working conditions are equally crucial.